Monitoring technological changes with statistical control charts based on patent data - Mutlu, Nazli Gulum; Altuntas, Serkan (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
Technology forecasting constitutes the basis of technology development and investment in technology. In a dynamic environment where technology is rapidly evolving and growing, the need to check the availability of a single prediction model has become an important research topic. The aim of this study is to follow the development of safety technologies in the field of occupational health and safety by using statistical quality control charts. Expanding the I-MR control chart rules used in monitoring the reliability of the technology forecasting model and considering the safety technologies in the field of occupational health and safety (OHS), which were previously discussed in the literature, are the original aspects of the study. At the beginning of the study, 91,580 patent data, was anlaysed using the United States Patent and Trademark Office (USPTO) database during including 1942-2020 (December) period. Time series modeling is performed using patent data on safety technologies, and I-MR graph is created using residual values of the model. The reliability of the model is monitored by controlling significant deviations with the obtained I-MR graphics. In addition, an S-curve is created for the patent numbers. The results of this study show that using a single technology forecasting model for a long period of time is misleading. Additionally, the forecast model for the period between 1942 and 2020 should be updated in various periods. Occupational health and safety technologies are an emerging technology field and appear to be incentives for policy makers and safety engineers to allocate resources.
Keywords: Statistical control chart; I-MR control chart; patent analysis; OCCUPATIONAL-HEALTH; EMERGING TECHNOLOGIES; REGRESSION-MODEL; SAFETY; SYSTEM; COMBINATION; DOCUMENTS; INTERNET; RISKS; TOOL; Engineering